Bioactive seaweeds for food applications natural ingredients for healthy diets (ELSEVIER ACADEMIC PRESS, 2018)
Bioactive Seaweed Substances for Functional Food Applications: Natural Ingredients for Healthy Diets presents various types of bioactive seaweed substances and introduces their applications in functional food products. Presenting summaries of the substances derived from seaweed, this book systematically explores new ingredients and the bioactive substances that are both environmentally friendly and highly beneficial to human health. This evidence-based resource offers an abundance of information on the applications of seaweed as a solution to meet an increasing global demand for sustainable food sources. It is an essential reference for anyone involved in seaweed substance research, seaweed processing, and food and health disciplines - Resumé vydavatel
Keywords: biotechnologie; potraviny; biologicky aktivní látky; mořské řasy; biotechnology; foodstuffs; bioactive compounds; seaweeds; kolektivní monografie; elektronické knihy; collective monographs; electronic books